The Influence of the Practice of Infiltrating Moral Education in Physical Education Teaching on Students’ Psychological Health - Yafei Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The aim of this study was to investigate the effect of integrating moral education into physical education curricula on students' mental health. To achieve this, a combination of teaching experiments, psychological assessments, surveys, and statistical analyses were employed to examine how moral education integration in physical education could enhance the mental health of 60 college students enrolled in four public physical education classes at a university in 2020. Following a 12-week instructional intervention, the experimental group's mental health scores across various indicators decreased compared to their pre-experiment levels. Post-experiment comparisons between the experimental and control groups revealed significant differences in mental health indicators, with the experimental group exhibiting a greater reduction in scores across all measures. These findings suggest that the incorporation of moral education into physical education effectively fosters positive mental health development among college students.